E-Commerce dan Dropshipping dalam Perspektif Fiqih Muamalah - Miranti, Lily; Maulida, Nurannisa; Setyanoor, Erwan (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2026)
The development of digital technology has driven significant transformations in the global trade system, particularly through e-commerce. One rapidly growing business model in the e-commerce ecosystem is the dropshipping system, a buying and selling mechanism in which sellers do not keep inventory but instead forward orders to suppliers. While offering convenience and efficiency, this practice raises various legal issues from a muamalah (Islamic jurisprudence) perspective, particularly regarding ownership of goods, clarity of contracts, and the potential for elements of gharar and tadlis. This study aims to analyze the concepts of e-commerce and dropshipping based on the principles of muamalah (Islamic jurisprudence) and to explain the forms of contracts that can be used to ensure compliance with Islamic law. The research method used is qualitative research with a normative approach through a literature review of classical and contemporary fiqh literature. The results indicate that e-commerce is fundamentally permissible in Islam as long as it meets the pillars and requirements of the contract. Dropshipping is also permissible provided that an appropriate contract is used, such as wakalah (a contract of sale), salam (a contract of sale), or samsarah (a contract of sale), and the application of the principles of honesty, transparency, and responsibility towards consumers.